Efeito de diferentes rações comerciais sobre o desempenho e parâmetros hematológicos de rã-touro, Rana catesbeiana - Fenerick Junior, Jaime [UNESP] (Universidade Estadual Paulista (Unesp), 2004)
This work evaluated the development of bullfrog, Rana catesbeiana, fed with four commercial rations, with presented analyzed crude protein ranging from 41.5% to 45.0% and energy ranging from 4,143 to 4,481 kcal/kg. Six hundred bullfrogs with initial medium weight varying from 12.6g to 28.0g were used for evaluation of growth, consumption, hepatossomatic index (HIS) and fatty somatic index (FSI), in five monthly samples. The worst growth result was observed in frogs fed with R4, presenting smaller weight gain and food consumption. No significant differences were observed among the rations for the food conversion, hepatic lipid and hepatossomatic index. In addition, a larger fatty somatic index was observed in frogs that received R2, with a tendency of increase of this index along the time, in all treatments

O presente trabalho visou estudar o desenvolvimento da rã-touro, Rana catesbeiana, alimentada com quatro rações comerciais, que apresentavam teores de proteína bruta analisada variando de 41,5 a 45,0% e energia bruta calculada entre 4.143 a 4.481 kcal/kg. Seiscentas rãs com peso médio inicial variando de 12,6g a 28g foram utilizadas para avaliação do desempenho zootécnico, glicemia, do índice hepatossomático (IHS) e do índice gordurassomático (IGOS), em cinco coletas mensais. O pior desempenho foi observado em rãs alimentadas com a ração R4, apresentando menor ganho de peso e consumo de ração. Não foram observadas diferenças significativas entre as rações para conversão alimentar, lipídio hepático e IHS. Também foi observado um maior IGOS nas rãs que receberam R2, com tendência de aumento deste índice com o tempo em todos os tratamentos
Keywords: Rã - Alimentação e rações; Rã touro; Desempenho; Hematologia; Lipídios; Frogs